PERAN KEADILAN DAN AGAMA BAGI MASYARAKAT SOSIAL DI INDONESIA - Winata, Lusyana Yosepha; Eddy Danukusumah; Sianipar, Rikardo P. (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2023)
This research aims to increase the importance of activities in religion. Hope that this research can make up an active role in realizing national development, to increase the awareness and morality regarding the importance of religious life in creating a balance between moral values ​​towards God and love towards others. To answer this question, qualitative research was carried out using a literature approach which aims to determine the role of religion and justice in social society. The relationship between the role of religion and government must be focused on the interests of society based on current and future needs. Social justice is expected to emerge from within society in order to create a civil society that maintains the stability of the country's economic, social and cultural values.Religion supports government programs that is used to achieve overall social justice.